FINDING COMMON GROUND: THE INTEGRATION OF EMPIRICISM AND RATIONALISM IN ISLAMIC RELIGIOUS EDUCATION TO ENHANCE LEARNING QUALITY - Permana, Rizal; Baari, Rosmalati Muthiatil; Parhan, Muhamad; Ilyasa, Faisal Fauzan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study explores the integration of empiricism and rationalism and its implications for Islamic Religious Education. Using a qualitative approach and literature study method, it analyzes the perspectives of empiricism and rationalism in the philosophy of science and their relevance to religious teaching. The study reviews classic works of philosophers like John Locke and René Descartes, alongside contemporary literature. Findings reveal that the empirical approach, emphasizing experience through worship and socio-religious activities, enhances students' understanding of religious teachings. Simultaneously, rationalism fosters critical reflection, enabling students to logically analyze and connect religious teachings with contemporary life. Integrating these approaches in the PAI curriculum creates holistic, effective, and practical learning. Theoretically, this supports the development of integrated religious education concepts, while practically, it encourages contextual teaching methods relevant to current challenges. However, the study is limited in its scope of application across diverse school types and does not assess the long-term impact of this integration. Future research should include longitudinal studies to evaluate the effectiveness of this integration in improving students' understanding and application of religious teachings across varied educational contexts. This would further enrich the conceptual and practical framework of Islamic Religious Education.